The Relationship between the Distribution of General Practitioners and the Mortality Rate of Children Based on the Gini Coefficient and Lorenz Curve - Majid Hajimaghsoudi; Najmeh Baghian; Mehdi Raadabadi (Shahid Sadoughi University of Medical Sciences, 2018)
Background: Equity is one of the most important issues in the distribution of resources and access to health services. Although it is very challenging to address health equity issues, it deeply affects policy making, resource allocation, and generally the legal principles of government and society. This study aimed to determine the inequality of distribution of general practitioner in Tehran province. Methods: This was an applied study that by ecological descriptive method investigated the relationship between the distribution of general practitioners and the mortality rate of children in the cities of Tehran province in 2012-2015. The data collection tool was a researcher-made form including the name of the city, the number of general practitioners, the mortality rate for children under five years old, and the population of each city. The STATA software with the DASP21 version 2.1 was used to draw the Lorenz curve. The SPSS19 software and Pearson correlation coefficient (P-value < 0.05) were utilized for analyzing data. Results: Based on the results the Gini coefficient for general practitioners was not significantly changed and was in a relatively equitable position, the Gini coefficient varied from 0.269 to 0.299. The results of the study did not show a significant relationship between the distribution of general practitioners and the mortality rate of children, although, with an increase in the ratio of general practitioners, the mortality rate of children decreased (P-value ≤ 0.05). Conclusion: The results of the study indicate that the distribution of general practitioners was relatively inequitable. Therefore, it is essential for the Ministry of Health to establish the balance in the distribution of the human resources